Atypical presentation of gastrointestinal stromal tumor masquerading as a large duodenal cyst: A case report. (2015) - Kumar, Ameet; Jakhmola, C.K.; Chauhan, Shivraj Singh; Singh, Apoorv
Highlights: Gastrointestinal stromal tumors (GIST) are solid tumors. Atypical presentations in form a cystic lesion have been rarely reported. A duodenal GIST masquerading as a cystic lesion has never been reported. First report a case of a large duodenal cyst that finally, turned out to be a GIST. Successfully managed by local resection avoiding a pancreaticoduodenectomy. Abstract: Introduction: Gastrointestinal stromal tumors (GIST) are solid tumors. A duodenal GIST masquerading as a cystic lesion has never been reported. We report a large duodenal cyst that finally turned out to be a GIST and was managed without a pancreaticoduodenectomy (PD). Presentation of case: A 55 year old lady presented with painful lump in epigastrium. A CT scan revealed a large exophytic cystic lesion from the duodenum with a small solid component. An endoscopy showed a polypoid lesion in the second part of the duodenum adjacent to what looked like a diverticulum. A sleeve duodenal resection, duodeno-duodenostomy and pyloric exclusion was done. The histopathology was duodenal GIST. Discussion: This case posed diagnostic difficulty as it was thought to be either a duplication cyst or a diverticulum of duodenum. The odd point was the small solid component in it. We considered the possibility of a malignancy arising in these settings, which is has been occasionally reported. To our surprise, it turned out to be a GIST. An extensive literature search yielded only four reports that have reported cystic GISTS, all arising from the stomach or pancreas where they have been mistaken for pseudocysts or even a mucinous cystadenocarcinoma of the pancreas. This is the first report of a cystic GIST arising from the duodenum. Conclusion: GISTS can present as a predominantly cystic lesion and needs to be considered in the differential diagnosis of cystic lesions of the duodenum. Local resection is an attractive option in select cases and avoids a PD.